Strategie finansowania innowacyjnych przedsiębiorstw - Pomykalski, Przemysław (Financing strategy of innovative companies, 2006)
The paper concerns the issue of financing of innovative companies. The main assumption is based on the idea that innovation as a source of competitive advantage should be the basis for the construction of the development strategy, which in turn should be financed. The financing should take into account the strategic objectives, the price of financing, the collateral, numer of shares to be sold and future sources of financing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 143-149